2021
DOI: 10.1007/s10565-021-09677-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into sevoflurane-associated developmental neurotoxicity

Abstract: With the development of technology, more infants receive general anesthesia for surgery, other interventions, or clinical examination at an early stage after birth. However, whether general anesthetics can affect the function and structure of the developing infant brain remains an important, complex, and controversial issue. Sevoflurane is the most-used anesthetic in infants, but this drug is potentially neurotoxic. Short or single exposure to sevoflurane has a weak effect on cognitive function, while long or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 140 publications
0
30
0
Order By: Relevance
“…We also found that when rats were anesthetized with sevo urane at a concentration of 2.32% for 1.5 h, there was no signi cant correlation between the time of recovery of motor coordination and the duration of anesthesia, but anesthesia for less than 1 h resulted in a relatively prolonged period of anesthesia and awakening [9] . And some studies have found that sevo urane anesthesia is toxic to neurons in rodents, but the speci c mechanism is not yet known [10] . Therefore, in this experiment, healthy adult rats were selected to investigate the effects of sevo urane anesthesia at different concentrations and for different times on the blood concentration of free HFIP in the blood of rats and its relationship with the behavior of adult rats during the awakening period of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that when rats were anesthetized with sevo urane at a concentration of 2.32% for 1.5 h, there was no signi cant correlation between the time of recovery of motor coordination and the duration of anesthesia, but anesthesia for less than 1 h resulted in a relatively prolonged period of anesthesia and awakening [9] . And some studies have found that sevo urane anesthesia is toxic to neurons in rodents, but the speci c mechanism is not yet known [10] . Therefore, in this experiment, healthy adult rats were selected to investigate the effects of sevo urane anesthesia at different concentrations and for different times on the blood concentration of free HFIP in the blood of rats and its relationship with the behavior of adult rats during the awakening period of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…As with other anesthetics, the potential mechanisms by which sevoflurane causes neurotoxicity are controversial. A recent review specifically summarized its possible mechanisms, including nerve cell damage and death, tau protein phosphorylation, and neuroendocrine abnormalities ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since this discovery, preclinical investigations on how anesthetics affect the developing brain have grown significantly ( Lin et al, 2017 ; Jevtovic-Todorovic, 2018 ). For example, sevoflurane exposure at critical stages of development may result in neuronal apoptosis and cognitive impairments, according to experimental research on animals ( Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%